Generalized Cesaro difference sequence spaces of non-absolute type involving lacunary sequences - Et, Mikail (Elsevier Science Inc, 2013)
In this paper we introduce and examine some properties of the sequence spaces C(Delta(m)(v), theta, (p)), C[Delta(m)(v), theta, (p)], C-infinity(Delta(m)(v), theta, (p)), C-infinity[Delta(m)(v), theta, (p)], N-theta(Delta(m)(v), (p)), S-theta(Delta(m)(v)) and study various properties and inclusion relations of these spaces. We also show that the space S-theta(Delta(m)(v)) may be represented as N-theta(Delta(m)(v), (p)) space. (c) 2013 Elsevier Inc. All rights reserved.
Keywords: Difference sequence; Lacunary sequence; Statistical convergence